Exile Trauma and Gender Relevance in the Novel Pulang: Postmemory Studies Marianne Hirsch - Putra, Jalu Norva Illa; Rahmawati, Damay; Jia, Cao (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Inspired by the real-life experiences of Indonesian exiles, Leila S. Chudori's Pulang explores the journey of an exile of the New Order regime attempting to come to terms with the trauma of the 1965 tragedy, and the inherited trauma of his daughter, who returns to the country of her father’s birth amid political turmoil. This research focused on revealing the discourse of exile as a victim who transmits their trauma to a subsequent generation, as well as the position of gender in the formulation of transmission, affecting the identification of trauma inheritance. Hirsch’s postmemory perspective was employed to analyze the process of trauma inheritance, which was rarely found in Indonesian literary works, as were the historical descriptive, causality, and comparison methods. The trauma inheritance experienced by the first generation is the trauma of loss due to the 1965 tragedy, which was then passed down to a child. Familial transmission becomes the basis of trauma inheritance, strengthened by affiliate transmission, which was a work of authentication in Indonesia. Gender plays a role in the affectivity of transmission, wherein transmissions involving fathers (exiles) and daughters are just as trauma-creating triggers. It is noteworthy that affiliative transmission fosters intersubjectivity among non-exiled female characters who are closely connected to the first generation, thereby enhancing the inheritance of trauma more effectively than familial transmission. The first generation is exiled and identifies its trauma by remembering and bringing with it Indonesian features, in various forms. In contrast, the second generation does it more concretely by becoming a real Indonesian. These findings underpin how an exile's trauma stemming from the 1965 tragedy can be passed on to the second generation, through a transmission process, a journey back to Indonesia, and gender relevance. Pulang redefines an exile as a victim and as an effort for reconciliation.